أسلوب القسم في (جزء عم) دراسة بلاغية - Abulgasim, Abdulhadi Ahmed (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص أسلوب القسم من الأساليب الإنشائية ، ومفهومه في الاصطلاح لا يختلف كثيرا عن مفهومه اللغوي، حيث يكون القسم منصبا على القرآن الكريم والحديث النبوي الشريف ... ، وقد ورد القسم في العديد من الآيات ، تارة بلفظ ( الأيمانْ ) ، وتارة بلفظ ( الحَلِف ) ، وأحيانا تسبقه حروف القسم وهي : ( الباء ، التاء، الواو ) أي : ( بالله وتالله ووالله ) . وقد تنوع القسم في ( جزء عم ) ، منه ماجاء مفردا ، ومنه ماجاء متعددا ، ومنه ما اشتمل على النوعين داخلا في العديد من السور . وإذا كانت الحكمة من القسم هو أن يزداد المؤمن إيمانا ويقينا ، فإن درجة إيمانه لا تحتاج إلى دليل أو برهان ، فإيماننا بالله وتصديقنا بكتابه ، هو أساس العقيدة ، وركيزة الإيمان . هذا فيما يخص المؤمن ، أما الكافر فإذا كان الهدف من القسم إقناعه بالحجة والدليل ، فهو أصلا منكر وجاحد ومكذب بالقرآن . أما عن ضروب القسم في ( جزء عم ) فهذا موضوعنا الذي نحن بصدده ، وهو ما سنفصل فيه القول في دراسة بلاغية تهدف إلى الغرض المطلوب . وأي فصاحة أو بلاغة تعدل بلاغة القرآن الكريم أو ترقى إلى مستواه ...؟ Abstract The oath's style is one of the structural methods; its terminological concept does not differ much from its linguistic concept. Our study focuses on the oath in the Noble Qur’an and the noble Prophet’s hadith…. The oath was mentioned in many Quranic verses, sometimes with the word “faith”, and sometimes with the word “swearing”. Sometimes it is preceded by the letters of the oath, which are: ("bi","ta" and "wa") (biAllahi, taAllahi, and waAllahi) meaning: (to swear by Allah). The oath has varied in Juz Amma (Amma part), some of it came singly, some were multiple and some of it included both types as in many verses (surahs). If the wisdom of the oath is to increase the believer's faith and certainty, then the degree of his faith does not need evidence or proof, as our belief in Allah and his book is the basis of belief and the pillar of faith. That is with regard to the believer. While for the disbeliever, if the aim of the oath is to convince him of the argument and evidence, then it is already denounced, ungrateful, and denies the Quran. As for the types of swearing in (Juz Amma), this is our topic that we study, which we will elaborate on in a rhetorical study to reach the desired purpose. which eloquence can modify the rhetoric of the Noble Qur’an or rise to its level…?! It is clear to us through this study that the highest percentage of the swearing in Juz Amma came in the swearing with cosmic phenomena and what nature included in both its silent and moving types. Perhaps this is due to the fact that these phenomena are a great proof of the wonderful creation of Allah.